Nutrition and Female Fertility: An Interdependent Correlation - Silvestris, Erica; Lovero, Domenica; Palmirotta, Raffaele (Frontiers in Endocrinology, 2019)
Besides ageing, a number of non-modifiable lifestyle-related factors, as smoking, elevated consumption of caffeine and alcohol, stress, agonist sports, chronic exposure to environmental pollutants, and other nutritional habits exert a negative impact on women’s fertility. In particular, metabolic disorders including diabetes, obesity, and hyperlipidemia commonly associated to hypercaloric diets are suspected to promote infertility in women either by direct damage to oocyte health and differentiation, or by indirect interference with the pituitary-hypothalamic axis, resulting in dysfunctional oogenesis. Obese women show decreased insulin sensitivity determining persistent hyperinsulinemia, which may be involved in the pathogenesis of Polycystic Ovary Syndrome. Thus the reduced insulin secretion induced by dietary adjustments is an attractive non-pharmacological treatment for preventing infertility and the Mediterranean diet aimed at maintening normal body mass may be effective in preservation of ovarian health and physiology. Furthermore, in relation to the oxidative stress as a co-factor of defective oocyte maturation, an appropriate intake of proteins, antioxidants and methyl-donor supplements (1-Carbon Cycle) may decrease the bioavailability of toxic oxidants and protect the oocyte differentiation.